A Descriptive Study On English Teaching Learning Process At SMP Al- Azhar Syifa Budi Solo In 2011/2012 Academic Year - AZIZAH, NUR (2012)
This study to describe the teaching learning process on English at SMP Al- Azhar Syifa Budi Solo in 2011/ 2012 academic year which covers the learning objectives, the kinds of syllabus, the material, the methods of teaching, evaluation and the strengths and weaknnesses of teaching English learning process. The data of the research are in the form of excerpts transcribed from the teacher' attitude and interview. The writer takes the teacher who teaches the first year at SMP Al- Azhar Syifa Budi Solo as subject of the research. The writer uses descriptive qualitative especially ethnography in analyzing the data. The study shows that the learning objective of teaching English is to develop communicative skills for the expression of basic needs and for basic interactive skills, especially in the academic context. The syllabus used by the teacher is theme based syllabus. The material used by the teacher not only comes from textbooks but also CD or cassette and internet. The method of teaching English is divided into three types, namely Grammar Translation Method, Community Language Learning and Communicative Language Teaching. The evaluation system includes daily test, assignment, mid test and final test. In general, English teaching learning process is appropriate with syllabus and the techniques used by the teacher are varied, so it makes students motivated to be active in classroom. But, actually the teacher cannot control the students in the classroom, since the instructions are unclear, and the exercises that given by the teacher are not varied